Folk Medicine in the Philippines: A Phenomenological Study of Health-Seeking Individuals - Nadine Angela Rondilla; Ian Christopher N. Rocha; Shannon Jean Roque; Ricardo Martin Lu; Nica Lois B. Apolinar; Alyssa A. Solaiman-Balt; Theorell Joshua Abion; Pauline Bianca Banatin; Carina Viktoria Javier (University Library System, University of Pittsburgh, 2021)
Background: Folk medicine refers to traditional healing practices anchored on cultural beliefs of body physiology and health preservation. Reflective of indigenous heritage, it fosters a better understanding of health and disease, healthcare systems, and biocultural adaptation. In the Philippines, Quiapo is a well-known site for folk medicine services, cultural diversity, religious practices, and economic activities. Methods: This study utilized a phenomenological approach to comprehend the lived experiences of health-seeking individuals and the meaning behind their acquisition of folk medicine products. Using convenience sampling, seven participants acquiring folk medicine products in Quiapo on the day of data collection were approached and interviewed on separate instances. The collected data subsequently underwent thematic analysis. Results: Analysis revealed three emergent themes: health-seeking behavior, sources of knowledge, and folk medicine utilization. Health-seeking behavior was linked with the participants' purpose of going to Quiapo, reasons for utilizing folk medicine, experiences in using folk medicine, and beliefs associated with the product bought. Sources of knowledge tackled the participants' sources of information about Quiapo and its products. Folk medicine utilization relates to the type of product bought, its perceived medicinal use, and its history of usage. Conclusion: Folk medicine is perceived to be effective alleviating health concerns. The acquisition of such products is attributed to satisfaction from prior experience, distrust in the current healthcare system, family tradition, and intention to supplement existing medical treatment. This study provides health professionals a better understanding of patients who patronize folk medicine, subsequently aiding them in providing a holistic approach to treatment.